INSTAGRAM CONTENT STRATEGY FOR ESPORTS EVENTS @mpl.id.official IN INCREASING ESPORTS TOURISM - Wahyudi, Fizar; Kencana, Woro Harkandi (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
Esports, as a form of sports that involves players interacting through computer media, has experienced rapid growth thanks to the development of online games and online broadcasting technology. The esports industry has now evolved into a sports and entertainment tourism that attracts the interest of many people. This research discusses the social media content strategy of the @MPL.ID.OFFICIAL esports e vent in increasing esports tourism interest in Indonesia. A qualitative descriptive approach is used with data collection techniques through interviews and observations. Semi-structured interview methods are used to analyze content strategies on the Instagram account @mpl.id.official using the AISAS theory as the analytical framework. The research results show that in the Attention aspect, the MPL Indonesia team successfully captures the audience's attention by presenting content that involves popular teams and players with large fan bases. In the Interest aspect, the MPL Indonesia team fulfills the audience's needs by providing informative content related to MPL Indonesia. In the Search aspect, the MPL Indonesia team uses content reposting and tagging strategies on talents and professional players. In the Action aspect, it can be concluded that focusing on timely information updates plays a crucial role in attracting followers' interest in the MPL Indonesia social media content strategy. Lastly, in the Share aspect, the MPL Indonesia team successfully creates content that can be easily shared by followers, especially content related to Mobile Legends, which has high potential for sharing.